Types of Sentences in EFL Students' Paragraph Assignments: A Quantitative Study on Teaching and Learning Writing at Higher Education Level - Sukandi, Syayid Sandi; Merina, Yola (Journal of Education Reseach and Evaluation, 2017)
This research investigates Indonesian EFL students writing four types of English sentences in their paragraph writing assignments that were posted online in Writing 1 course of English Education at STKIP PGRI Sumatera Barat. The analysed types of sentences are Simple Sentence (code: S.S.), Compound Sentence (code: C.S.1), Complex Sentence (code: C.S.2), and Compound-Complex Sentence (code: C.C.S). The percentage of each type of sentences that appears in the students’ writings within each five genres represents the students’ syntactical composition. Moreover, this research focuses on quantitatively analysing the above five types of sentences that appeared in students’ assignments in each type of following genres: argumentative, descriptive, process, cause-effect, and comparison-contrast. Data are taken from 10% samples of all population. The finding shows that writing Simple Sentence in paragraphs is a common type of sentence that is used by the students. It indicates that the guiding process to teaching students about writing paragraphs with varied sentence types is important for further development of teaching process of writing.